Functionalized magnetite nanoparticle coagulants with tropical fruit waste extract: a potential for water turbidity removal - Praveena, Sarva Mangala; Kuan, Crystal Xin Yi; Ying, Josephine Chyi Liew; Md Firoz Khan (Springer, 2022)
This study explored the potential of functionalized nanoparticles with active compounds extracted from tropical fruit wastes to increase the performance of turbidity removal from the water of natural coagulants. Extracts from banana, durian, and jackfruit wastes (peel and seed) were tested for their coagulation activity. Banana peel extract had the highest coagulation activity of 70% and was functionalized with magnetite nanoparticles and characterized with X-ray diffraction and Fourier transform infrared spectroscopy. Analysis of variance showed the mass and settling time of the functionalized nanoparticle as significant parameters associated with water turbidity removal. Response surface methodology using the Box–Behnken design (BBD) for tropical fruit wastes indicated that a linear model was able to describe the effects of the parameters (tropical fruit mass, nanoparticle mass, and settling time) on the response (turbidity removal). Optimized parameters via BBD for tropical fruit mass, nanoparticle mass, and settling time were 0.26 g, 14.37 mg, and 25 min, respectively. Field sample tests showed turbidity removal percentages using the functionalized magnetite nanoparticle with banana peel extracts were between 88.5 and 92.8%. The performance efficacy score of functionalized magnetite nanoparticles with banana peel extract as the coagulant showed promising potential as a water turbidity removal during an emergency.